Domesticating the condition: Design lessons gained from a marathon on how to cope with barriers imposed by type 1 diabetes - Montt-Blanchard, Denise; Dubois-Camacho, Karen; Costa-Cordella, Stefanella; Sánchez, Raimundo (Frontiers in Psychology, 2022)
Through analytical autoethnographic analysis of marathon preparation, this study examines challenges faced by people with Type 1 Diabetes (T1D) who engage in high-performance sports. Autoethnographer and second-person perspectives (T1D runners, family members, and health providers) were collected through introspective activities (autoethnographic diary and in-depth interviews) to understand the T1D runner’s coping experience. Six insights involved in T1D self-management were identified and analyzed with reference to related design tools (prototyping, archetyping and journey mapping). Finally, we conclude with a discussion of how endurance physical activity (PA) such as running helps to “domesticate” T1D, a term coined to reflect the difficulties that T1D presents for PA accomplishment and how T1D runners’ experiences give them an opportunity to overcome PA barriers promoting physical culture and enriching further health psychology studies.